A case of treatment-induced neuropathy in an adolescent with type 1 diabetes - Niranjana Varadharaju; Dhivyalakshmi Jeevarathnam; Mahalakshmi Rajan; Vinoth Ponnurangam Nagarajan; Saji James (Korean Society of Pediatric Endocrinology, 2019)
Treatment-induced neuropathy (TIN) in diabetes is an acute and painful yet completely reversible small fiber neuropathy precipitated by a rapid improvement in glycemic control. TIN is rare in children. A 16-year-old girl developed symmetrical painful neuropathy of the foot, autonomic neuropathy, and retinopathy 5 weeks after the diagnosis of type 1 diabetes. All causative workups were negative except for a drop-in hemoglobin A1c (HbA1c) from 17.4% to 7%, which fit with a diagnosis of TIN. Following symptomatic management, her neuropathy and retinopathy completely resolved in 2 months. Currently, she is 18 years old and doing well (HbA1c, 7.4%) without any recurrence of TIN. TIN should be suspected in any child presenting with recent-onset type 1 diabetes and acute onset neuropathy. Our case represents an unreported scenario of the rapid progression in TIN. Awareness among clinicians about this rare but completely reversible condition is necessary to ensure proper management and adherence to glycemic control.